2020
DOI: 10.1002/app.49633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection molding on structure and properties of poly(styrene‐ethylene‐butylene‐styrene) and its nanocomposite with functionalized montmorillonite

Abstract: In this paper, the effects of injection molding on structure and properties of poly(styrene-ethylene-butylene-styrene) (SEBS) and its nanocomposite with a functionalized montmorillonite (FMMT) were illustrated by comparison with the results of hot pressing. The injection-molded SEBS and its FMMT nanocomposite have a skin-core morphology with FMMT platelets more preferentially aligned along the sample plane, while hot-pressed samples not. The injection-molded samples also have a dense structure, and a less exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…5,6 In nanoinjection molding, interface bonding strength is considered a key property of composite materials, with lowperforming interfaces often leading to extensive failure in the interface structure of the composite material. Li et al 7 investigated the impact of injection molding on the structure and properties of poly(styrene-ethylene-butylene-styrene) (SEBS) and its nanocomposites with functionalized montmorillonite (FMMT). It showed that the long alkyl silane chains grafted to FMMT exhibited favorable interactions with the soft segments of SEBS, resulting in the formation of a better SEBS/ FMMT interface.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In nanoinjection molding, interface bonding strength is considered a key property of composite materials, with lowperforming interfaces often leading to extensive failure in the interface structure of the composite material. Li et al 7 investigated the impact of injection molding on the structure and properties of poly(styrene-ethylene-butylene-styrene) (SEBS) and its nanocomposites with functionalized montmorillonite (FMMT). It showed that the long alkyl silane chains grafted to FMMT exhibited favorable interactions with the soft segments of SEBS, resulting in the formation of a better SEBS/ FMMT interface.…”
Section: Introductionmentioning
confidence: 99%
“…Several conventional polymer processing techniques, including fiber spinning, [97] film blowing, [98] and uniaxial stretching, [103] can be employed to introduce sufficient mechanical force for orienting fillers within the composite. Shearing is also involved in injection molding, [104][105][106][107] plate shearing, [108] and roll-milling, [109][110][111] which can provide an alternative mechanism to develop directional assembly of particles in the polymer matrix. Additionally, application of external fields can polarize fillers, resulting in their alignment within a matrix along the field direction.…”
Section: Introductionmentioning
confidence: 99%
“…Sengupta et al 20 found that the PP phase can be dispersed into the polystyrene domain under high strain, and can be oriented together with SEBS to increase the elongation of the ternary blend. Our previous work found that due to the high‐shear flow, injection‐molded SEBS and its nanocomposite have a skin‐core morphology, and the relaxation of molecular chains is limited by the mold, the degree of microphase separation is greatly reduced, and the tensile strength and corrosion resistance are greatly reduced 21 . In injection molding, high‐speed shear can untie the entangled molecular chains of the triblock copolymer, reduce its melt viscosity, improve its mold filling ability, and obtain good mechanical properties 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work found that due to the high-shear flow, injection-molded SEBS and its nanocomposite have a skin-core morphology, and the relaxation of molecular chains is limited by the mold, the degree of microphase separation is greatly reduced, and the tensile strength and corrosion resistance are greatly reduced. 21 In injection molding, high-speed shear can untie the entangled molecular chains of the triblock copolymer, reduce its melt viscosity, improve its mold filling ability, and obtain good mechanical properties. 22 However, the anisotropy caused by shearing makes the polymer chain in an unbalanced stress conformation, 23 which is prone to form microscopic defects and macroscopic dimensional changes under external stimulation.…”
Section: Introductionmentioning
confidence: 99%